Evaluation of a Genetics Education Program for Health Interpreters: A Pilot Study - Vidgen, Miranda E.; Fowles, Lindsay F.; Istiko, Satrio Nindyo; Evans, Erin; Cutler, Katrina; Sullivan, Kate; Bean, Jessica; Healy, Louise; Hondow, Gary; McInerney-Leo, Aideen M.; Pratt, Gregory; Robins, Deborah; et al. (Frontiers in Genetics, 2022)
Health Interpreters enable effective communication between health practitioners and patients with limited knowledge of the predominant language. This study developed and evaluated a training session introducing Health Interpreters to genetics. The online training was delivered multiple times as a single 2-h session comprising lectures and activities. Participants completed questionnaires (pre-, post-, and 6-months follow-up) to assess the impact of training on knowledge, attitude, self-efficacy, and self-reported practice behaviour. Questionnaires were analysed using descriptive statistics, Fisher’s Exact, or independent t-test. In total, 118 interpreters participated in the training sessions. Respondent knowledge improved, with gains maintained at 6-months (p < 0.01). There were no changes in self-efficacy, and attitudes. Training did not change self-reported practice behaviour, but there was notable pre-existing variability in participants’ methods of managing unknown genetic words. Most respondents agreed that training was useful (93%) and relevant (79%) to their work. More respondents reported learning more from the case study activity (86%) than the group activity (58%). Health Interpreters found the training acceptable and demonstrated sustained improvement in knowledge of genetic concepts. Increased delivery of this training and associated research is needed to assess findings in a larger cohort and to measure the impact on patients.